Optimal Taxation: The Design of Child Related Cash- and In-Kind-Benefits - Peter Haan; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper contributes to the debate about the optimal design of tax-transfer systems. Based on the theory of optimal taxation, combined with microsimulation and microeconometric techniques we derive the welfare function which makes the current German tax and transfer system for single women optimal. Furthermore, we compare the welfare function conditional on the presence and age of children and asses how reforms of in-kind childcare transfers would affect the welfare function. This analysis allows us to derive conclusions about the optimal design of child related transfers and in-kind benefits.
Keywords: C23; C25; J22; J64; 330; Optimal taxation; labor supply behavior; transfers for children